Effect of COVID-19 Pandemic on Traditional Teaching - Ghosh, Mitali; Jansz, Janis; Ghosh, Apurna (2022)
COVID 19 made a great impact on education system especially on the university education system globally. The purpose of this systematic review of published literature was to trace the history of university teaching and examine the effects of the COVID 19 pandemic on traditional teaching. Systematic review started with 720 articles and ended with the inclusion of 136 articles based on bibliometric search process. Important understandings generated are that educational methods are constantly evolving as what the ruling society values changes and when new technologies that can be used for teaching are invented. Conclusions were that this deadly pandemic overturned the traditional offline teaching and learning process and facilitated the introduction of emergency online educational platforms to be used for university teaching and student learning.